Management of anticoagulation in patients with human immunodeficiency virus/acquired immunodeficiency virus. Issue 200 (April 2021) - Sabourin, Ashley A.; Patel, Twisha; Saad, Samira; Renner, Elizabeth; Mouland, Erin; Adie, Sarah; Ha, Nghi B.
Abstract: Purpose: Limited guidance is available to assist practitioners in managing complex human immunodeficiency virus (HIV) related pharmacotherapy. Management recommendations of oral anticoagulation (warfarin and direct oral anticoagulants [DOACs]) and highly active antiretroviral therapy (HAART) based on drug-drug interactions (DDI) studies and pharmacokinetic (PK) data are provided. Methods: Search of PubMed, EMBASE, and Google Scholar (01/1985 to 12/2018) using the terms "HIV, " "DDI, " and names of HAART. PK information and DDI screening were obtained from medication package inserts and drug information resources: Micromedex, Lexicomp, HIV-DDI Checker- University of Liverpool. All English literature on DDI or PK interactions was considered for inclusion. In the absence of data, PK principles were used to predict the likelihood of interactions. Results: No clinically significant DDI are expected to occur between DOACs and nucleoside or nucleotide reverse transcriptase inhibitors (NRTIs), maraviroc, enfuvirtide, or integrase strand inhibitors (INSTIs) that do not include a pharmacologic booster. Potent cytochrome P (CYP) 450 enzyme inhibition by protease inhibitors (PIs) or pharmacologic boosters may lead to higher concentrations of the DOAC and potentially increase the risk of bleeding. CYP450 enzyme induction by non-nucleoside reverse transcriptase inhibitors (NNRTIs) may lower concentrations of DOACs, which may lead to treatment failure. Warfarin DDIs are variable, therefore close monitoring of the INR is recommended. Conclusions: The potential for DDIs between HAART and oral anticoagulation exists based on PK profiles. Management of these interactions should involve careful selection based on patient characteristics and HAART and anticoagulants with a low potential for DDI should be selected. Highlights: No clinically significant DDI between DOACs andNRTIs, maraviroc, enfuvirtide, or INSTIs that do not include a pharmacologic booster. Potent CYP450 inhibition by PIs or pharmacologic boosters may lead to higher concentrations of the DOAC and potentially increase the risk of bleeding. CYP450 enzyme induction by NNRTIs may lower concentrations of DOACs, which may lead to treatment failure.